PERAN PEMERINTAH DAERAH DALAM PENANGGULANGAN BENCANA - Sri Heryati (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2020)
Natural disaster keeps occurring in Indonesia: earthquake, landslide, flood, forest fire, even drought. The effects are not only material loss, but also death and ecosystem loss. This writing would discover government role in disaster handling and the obstacles. Analysis was based on several researches with similar topic. Therefore, the study applied desk research technique. Based on the result, it was found that government has shown their role in disaster handling through 5 (five) aspects: legislative, agency, planning, financial, and capacity development. In this case, government has taken strategic attempt to deal with natural disaster risk and effects by building BNPB in central level and BPBD in regional level. This non-department agency has become a leading sector in disaster handling. It was also known that almost every region face similar obstacle in disaster handling: limited budget, human resource, tools and equipment; and lack of inter-sector coordination Keywords: Government Role; Disaster Management